2019
DOI: 10.1111/ppe.12572
|View full text |Cite
|
Sign up to set email alerts
|

Risks of preterm birth among non‐Hispanic black and non‐Hispanic white women: Effect modification by maternal age

Abstract: Background Preterm birth (PTB) disproportionately affects African American compared with Caucasian women, although reasons for this disparity remain unclear. Some suggest that a differential effect of maternal age by race/ethnicity, especially at older maternal ages, may explain disparities. Objective To determine whether the relationship between maternal age and preterm birth varies by race/ethnicity among primiparae non‐Hispanic blacks (NHB) and non‐Hispanic whites (NHW). Methods A cross‐sectional study of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 52 publications
3
9
0
Order By: Relevance
“…This sustained gradient effect of maternal age supports previous evidence on the importance of social, economic, and behavioural factors that predispose some young women to pregnancy, rather than biological immaturity, in explaining disparities in infant outcomes for teenage mothers 18 . It also contributes to the debate on maternal weathering, which posits that lifelong exposure to social and environmental disadvantage leads to broader disparities in health outcomes among disadvantaged populations 14,19 . Infants born to mothers aged <25 years represent a large proportion of births, particularly in England and Scotland (around 20%, compared with 15% in NSW and Ontario, and 13% in Sweden; Table ).…”
Section: Commentsupporting
confidence: 79%
“…This sustained gradient effect of maternal age supports previous evidence on the importance of social, economic, and behavioural factors that predispose some young women to pregnancy, rather than biological immaturity, in explaining disparities in infant outcomes for teenage mothers 18 . It also contributes to the debate on maternal weathering, which posits that lifelong exposure to social and environmental disadvantage leads to broader disparities in health outcomes among disadvantaged populations 14,19 . Infants born to mothers aged <25 years represent a large proportion of births, particularly in England and Scotland (around 20%, compared with 15% in NSW and Ontario, and 13% in Sweden; Table ).…”
Section: Commentsupporting
confidence: 79%
“…This study highlighted a rising trend for preterm birth rate in Taiwan from 2004 to 2013. This finding was consistent with those of previous studies [29,30]. We found that provider-initiated preterm delivery was positively associated with the occurrence of preterm birth in this study.…”
Section: Discussionsupporting
confidence: 94%
“…Environmental and clinical factors such as toxicant particulate matter (PM 2.5–10, bisphenol, etc. ), consumption of a high-fat diet, family PTB history, low education, low socioeconomic status, ethnicity (PTB is higher in non-Hispanic black women), previous PTB history, multiple pregnancies, short pregnancy interval, early (<16 years) or late (>36 years) pregnancy, tobacco or alcohol consumption, high stress, hypertension, obesity, low body mass index, infection, short cervix, uterine anomaly, and miscarriage can affect fetal developmental plasticity, gestational age, or birth outcome [ 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%